EDUCATING CATTLE FARMERS TO SUSTAINABLY INCREASE THEIR INCOME IN SOUTHEAST ACEH - Muttaqinullah; Joharsah; Hadirin; Kartono; Sudarma JA; Zaini Hasan; Desti PZ; Carli; Seroja S; Abdi R; Harapin HH; Subaedah S (Jurnal Pengabdian Bangsa, 2026)
Cattle farming is one area with great potential to boost the local economy in Southeast Aceh, especially in Ketambe District. However, many farmers still face various problems, including a lack of knowledge in animal care management, feeding their cattle improperly, poor disease control, and limited skills in managing their business and marketing their livestock products. This situation results in low productivity and income for the farmers, so ongoing education programs are needed. This community service activity aims to improve the knowledge, skills, and capacity of 60 beef cattle farmers in Ketambe District, Southeast Aceh, so they can apply good farming practices and develop their livestock businesses sustainably. The methods used in this activity include counseling, training, and mentoring. Counseling is done by providing information about beef cattle maintenance management, feed formulation, animal health, reproduction, and business management. Training focuses on skills in making alternative feed, implementing biosecurity, and recording farm business activities, while mentoring aims to ensure the application of technology and business management among farmers. The results of the activities are evaluated through observation and comparing the participants' understanding before and after the activities. The results of the activity showed an increase in farmers' knowledge and skills regarding the management of beef cattle, the use of local feed resources, disease prevention efforts, and business record-keeping. In addition, farmers started to adopt more efficient farming practices, which could boost livestock productivity, reduce production costs, and strengthen the sustainability of their farms. The level of enthusiasm and active participation from all participants during this activity was a clear sign of the program's success.